Fine mapping of qSS‐9, a major and stable quantitative trait locus, for seed storability in rice (Oryza sativa L.). Issue 3 (8th April 2015) - Lin, Qiuyun; Jiang, Yimei; Sun, Ailing; Cao, Penghui; Li, Linfang; Liu, Xi; Tian, Yunlu; He, Jun; Liu, Shijia; Chen, Liangming; Jiang, Ling; Ahn, S.N.
Abstract Seed storability in rice (Oryza sativa L.) is an important agronomic trait. We previously showed a quantitative trait locus of seed storability, qSS‐9, on chromosome 9 in a backcross population of 'Koshihikari' (japonica) / 'Kasalath' (indica) // 'Koshihikari'. In this study, fine mapping of the chromosomal location of qSS‐9 was performed. Effect of 'Kasalath' allele of qSS‐9 was validated using a chromosome segment substitution line, SL36, which harboured the target quantitative trait loci (QTL) from 'Kasalath' in the genetic background of 'Nipponbare' under different ageing treatments in different environments. Subsequently, an F2 population from a cross between 'Nipponbare' and SL36 was used for fine mapping of qSS‐9. Simultaneously, four subnear isogenic lines (sub‐NILs) that represented different recombination breakpoints across the qSS‐9 region were developed from F3 progeny. Finally, the qSS‐9 locus was located between the Indel markers Y10 and Y13, which delimit a region of 147 kb in the 'Nipponbare' genome. These results provide a springboard for map‐based cloning of qSS‐9 and possibilities for breeding rice varieties with strong seed storability.